PENGARUH PEMBERIAN ANGKAK TERHADAP KENAIKAN JUMLAH TROMBOSIT TIKUS JANTAN - Christianus Heru Setiawan (Sanata Dharma University, 2015)
Abstract: The research has purpose to get information about the effect of water-boiled red yeast rice for raising the platelet levels so that it can be used as a supplement for patients of Dengue Hemorrhagic Fever (DHF). The research was pure experimental with direct sampling design. The research used Wistar male rats, age 2-3 months, and weight + 150-250 grams. Rats randomly divided into five treatment groups. First group (negative control) given CMC Na 1% 0.72 g/KgBW for 7 days followed by 2.5 mL of distilled water for 5 days. Second group (positive control) given chloramphenicol 0.72 g/KgBW for 7 days followed by distilled water for 5 days. Fourth-fifth group (treatment) given chloramphenicol dose 0.72 g/KgBW for 7 days followed by water-boiled red yeast rice dose 2; 1; and 0.5 g/KgBW orally for 5 days. Blood sampling taken on day 0 and day 12, blood taken from the sinus orbitalis eyes for measuring levels of platelet count. Platelet concentration data that got were analyzed by Shapiro-Wilk test to see the distribution of data. If data are normally distributed then continue the analysis with paired-samples t test analysis, if data is not normal distributed then followed by Wilcoxon test analysis to know the difference levels of platelets experiment by treatment and duration of the test. The results of this research showed that water-boiled red yeast rice has effect to increase platelet levels in male rats induced by chloramphenicol at a dose of 2; 1; and 0.5 g/KgBW and gived platelet levels increasing effect at rate of 18.78, 14.02, and 5.45%. Keywords : red yeast rice, platelets, chloramphenicol